Zinc metabolism and its role in immunity status in subjects with trisomy 21: chromosomal dosage effect - Ramacieri, Giuseppe; Locatelli, Chiara; Semprini, Michela; Pelleri, Maria Chiara; Caracausi, Maria; Piovesan, Allison; Cicilloni, Michela; Vigna, Marco; Vitale, Lorenza; Sperti, Giacomo; Corvaglia, Luigi Tommaso; Pirazzoli, Gian Luca; et al. (Frontiers in Immunology, 2024)
Trisomy 21 (T21), which causes Down syndrome (DS), is the most common chromosomal aneuploidy in humankind and includes different clinical comorbidities, among which the alteration of the immune system has a heavy impact on patient's lives.A molecule with an important role in immune response is zinc and it is known that its concentration is significantly lower in children with T21. Different hypotheses were made about this metabolic alteration and one of the reasons might be the overexpression of superoxide dismutase 1 (SOD1) gene, as zinc is part of the SOD1 active enzymatic center.The aim of our work is to explore if there is a linear correlation between zinc level and immune cell levels measured in a total of 217 blood samples from subjects with T21. Furthermore, transcriptome map analyses were performed using Transcriptome Mapper (TRAM) software to investigate whether a difference in gene expression is detectable between subjects with T21 and euploid control group in tissues and cells involved in the immune response such as lymphoblastoid cells, thymus and white blood cells.Our results have confirmed the literature data stating that the blood zinc level in subjects with T21 is lower compared to the general population; in addition, we report that the T21/control zinc concentration ratio is 2:3, consistent with a chromosomal dosage effect due to the presence of three copies of chromosome 21. The transcriptome map analyses showed an alteration of some gene's expression which might explain low levels of zinc in the blood. Our data suggest that zinc level is not associated with the levels of immunity cells or proteins analyzed themselves and rather the main role of this ion might be played in altering immune cell function.